Social sharing of emotion during the collective crisis of COVID-19 - Ma, G; Schone, J; Parkinson, B (Wiley, 2024)
We collected data from two sources – social media and online questionnaires – to investigate the emotional consequences of social sharing during the COVID-19 pandemic. Study 1 tracked and analysed sentiment of tweets posted over the course of a month in the crisis period and found that users who tweeted more frequently about COVID-19 expressed decreasing negative sentiment and increasing positive sentiment over time. Granger causality tests confirmed that this association was better interpreted in the forward direction (sharing levels predicting sentiment) than in the reverse direction (sentiment predicting sharing levels). Study 2 focused on immediate emotional consequences of sharing COVID-19-related events and found that participants reported improved overall affect about an event after sharing it, especially when that event was a personal experience rather than a news story. Reported positive feelings about both kinds of events were also significantly higher after sharing. Taken together, both studies suggested that social sharing is linked with emotional relief and may therefore help people to deal with their negative experiences during a persistent collective crisis.